Changing mechanical properties of photopolymerized, dityrosine-crosslinked protein-based hydrogels - Haas, Sandra; Körner, Saskia; Zintel, Laura; Hubbuch, Jürgen (Frontiers in Bioengineering and Biotechnology, 2022)
Hydrogels based on renewable resources are a promising class of materials for future applications in pharmaceutics, drug delivery and personalized medicine. Thus, optional adjustments of mechanical properties such as swelling behavior, elasticity and network strength are desired. In this context, hydrogels based on the biological raw materials bovine serum albumin and casein were prepared by dityrosine-crosslinking of their tyrosine residues through visible light-induced photopolymerization. Changing the tyrosine accessibility by urea addition before photopolymerization increased the storage modulus of the hydrogels by 650 % while simultaneously being more elastic. Furthermore, contributions of the buffer system composition, variation of protein concentration and storage medium towards mechanical properties of the hydrogel such as storage moduli, elasticity, fracture strain, compressive strength and relative weight swelling ratio are discussed. It could be shown, that changes in precursor solution and storage medium characteristics are crucial parameters towards tuning the mechanical properties of protein-based hydrogels.